Repurchase Tender Offers, Signaling, and Managerial Incentives - Vermaelen, Theo (Journal of Financial and Quantitative Analysis, 1984)
One of the main principles of corporate finance is that managers should maximize the market value of the outstanding securities. While it is realized that managers and security holders may have divergent objectives, it is generally assumed that various market forces keep managerial and shareholders' goals in line. Out of the extensive literature on this issue, three such market forces emerge. First, non-value-maximizing firms are prime targets for take-over bids (e.g., see [14]): bidding firms could acquire control over the shares of the target firm, replace the management, follow a value-maximizing strategy, and realize a profit from the resulting appeciation of the target shares. Second, outside shareholders may charge managers-owners ex ante by discounting stock prices for expected managerial expropriation, which may induce managers to accept various restrictions on their behavior (e.g., see [11]). Third, shareholders may charge managers ex post, indirectly via the discipline imposed by a competitive managerial labor market (e.g., [8]). Note the difference from the previous mechanism: Jensen and Meckling [11] assume that managerial wages are fixed so that all the adjustment for expected expropriation is reflected in stock prices (and, ultimately, in costly monitoring and bonding devices). In Fama's [8] model, all the adjustment occurs in the managerial labor market, so that the value of the firm remains unaffected by expected managerial expropriation.